2020
DOI: 10.6026/97320630016965
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects and lysosomal acidification in A549 cells by astaxanthin from Haematococcus lacustris

Abstract: Astaxanthin (AXN) is known to have health benefits by epidemiological studies. Therefore, it is of interest to assess the effect of AXN (derived from indigenous unicellular green alga Haematococcus lacustris) to modulate cell cycle arrest, lysosomal acidification and eventually apoptosis using in vitro in A549 lung cancer cells. Natural extracts of astaxanthin were obtained by standardized methods as reported earlier and characterized by standard HPLC and MS. Treatment of A549 cells with AXN (purified fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Yin et al reported that astaxanthin reduces lipopolysaccharide (LPS)-induced inflammatory cytokines and then abrogates allogeneic T cell proliferation [13]. The anticancer efficacy of AST was also reported by several authors [14][15][16][17][18]. Natural AST showed inhibitory effects against the proliferation of renal clear cell carcinoma and placental growth factor expression [14].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Yin et al reported that astaxanthin reduces lipopolysaccharide (LPS)-induced inflammatory cytokines and then abrogates allogeneic T cell proliferation [13]. The anticancer efficacy of AST was also reported by several authors [14][15][16][17][18]. Natural AST showed inhibitory effects against the proliferation of renal clear cell carcinoma and placental growth factor expression [14].…”
Section: Introductionmentioning
confidence: 97%
“…Natural AST showed inhibitory effects against the proliferation of renal clear cell carcinoma and placental growth factor expression [ 14 ]. Ramamoorthy et al reported that AST induces cell cycle arrest, lysosomal acidification, and apoptosis of A549 cells [ 15 ]. Also, Tsuji et al reported that glioblastoma progression in a murine orthotopic model was suppressed by oral administration of AST [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Our research team is involved in high-quality publications and has extensive knowledge to translate the experiments. [ 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 ] To date to the best of our knowledge, there are no proper reports available on marine actinobacteria Nocardiopsis sp. from which the melanin pigment is extracted.…”
Section: Introductionmentioning
confidence: 99%